Islamic Universality for Global Goodness: Integration of Fiqh and Sufism - Teten Jalaludin Hayat; Ma’sum Anshori (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
Since the beginning, Islam has promised universal and global goodness (raḣmah li al-‘ālamīn). It's just that in reality the goodness was still particular and local. This imbalance is caused by an unequal understanding between the dimensions of exoteric fiqh (body) and esoteric sufism (mind) which represents the human condition which consists of body and mind. Thus, this research is aimed at explaining the universality of Islam for global goodness through integration between both dimensions. This research is a library research. The method used is the thematic method, to explore and confirm a theory to its deepest intent. The analytical tool used for this purpose is content analysis. The results of the analysis show that the fiqh-exoteric dimension will produce physical goodness (maqāṣid al-syarī’ah), and the sufism-esoteric dimension will produce spiritual goodness (maqashid al-ṣūfiyyah), so that with the integration of the two, the goal of Islamic universality (maqashid al-dīniyyah) will be born.